Incidence and Risk Factors for Organ/Space Infection after Radiofrequency-Assisted Hepatectomy or Ablation of Liver Tumors in a Single Center: More than Meets the Eye - Karavokyros, Ioannis; Orfanos, Stamatios; Angelou, Anastasios; Meropouli, Antonia; Schizas, Dimitrios; Griniatsos, John; Pikoulis, Emmanouil (Frontiers in Surgery, 2017)
Introduction: Surgical site infections (SSI) and especially organ/space infection after resection or ablation of liver tumors are associated with increased morbidity and mortality. A secondary bloodstream infection is considered an organ/space infection but the exact prevalence is unknown. We aimed to investigate the incidence of Organ Space Infections (O/SI) and Blood Stream Infections (BSI) in a cohort of consecutive patients after liver resection or ablation, to seek for a possible connection between them and to search for potential risk factors. Materials and Methods: We reviewed all patients who underwent hepatic resection or intraoperative liver ablation between January 2012 and December 2016 in our department. We focused on age, gender, Child-Pugh score, preoperative biliary drainage, indication for surgery, type of resection, resection or ablation of tumor, need for bilioenteric reconstruction, additional procedure to hepatectomy, blood transfusion, operative time, postoperative admission to ICU and antibiotic chemoprophylaxis. All positive cultures from intraabdominal fluids and blood were recorded. O/SI and BSI were diagnosed by the criteria set by CDC. All variables were compared between the group with organ/space infection and the group without infection. Bloodstream infections were associated with these infections also. Results: 81 consecutive patients with a mean age of 64y.o. were enrolled. 15 patients presented a positive culture postoperatively: intraabdominal fluid in 8, blood cultures in 6 and both blood and intraabdominal fluid in 1 patient. The directly estimated incidence of O/SI amounted to 11.1%. Four blood cultures were secondary to O/SI, and the remaining 2 secondary to central line catheter. O/SI was diagnosed indirectly, through the BSI in an additional 4.9% of the patients, raising the incidence of SSI to 16%. Among the factors studied only admission to the ICU was found to be statistically significant as a risk factor for the development of O/SI (p=0.026). Conclusion: O/SI should be actively seeked for after liver surgery including blood cultures. Patients with affected physical status, comorbidities are in greater risk of developing organ/space infection.